A review of wastewater bacterial bio oxidation: Mechanisms, reactions, and behaviors - Al-Amshawee, S.; Mohd Yusri, Mohd Yunus (Universiti Malaysia Pahang, 2021)
The most overlooked biological process is the oxidation process, due to the poor technical understanding of bioremediation and the many unexplained biological mechanisms. As a matter of fact, wastewater companies favor the physical and chemical approaches over the biological means to ensure process performance. Biological oxidation provides environmentally friendly treatment with limited operational requirements. It has a tremendous ability to metabolize ammonia, H2S, phosphate, and ferrous iron under the right conditions. Bacterial communities attack these wastewater components through using oxygen as a strong electron acceptor, resulting in simplified forms of wastewater components (e.g., ammonia to nitrogen gas). This manuscript reviews in details the mechanisms of wastewater bacteria against various pollutants, with the possible reactions and behaviors. It also presents the benefits of utilizing wastewater microorganisms against different pollutants.